Nuclear quantum effects in fullerene–fullerene aggregation in water - Panahian Jand, Sara; Nourbakhsh, Zahra; Delle Site, Luigi (Frontiers in Chemistry, 2022)
We study the effects of quantum delocalization in space of the hydrogen atoms of water in the aggregation process of two fullerene molecules. We consider the case where a purely repulsive water-fullerene interaction is used, since it has been shown that in such a situation water-mediated effects play the key role in the aggregation process. This study becomes feasible, at a reduced computational price, because the Path Integral (PI) Molecular Dynamics (MD) Method is combined with a recently developed open system MD technique. Specifically, only the mandatory solvation shell of the two fullerene molecules is considered at full quantum resolution while the rest of the system is represented as a mean-field macroscopic reservoir of particles and energy. Our study shows that the quantum nature of the hydrogen atoms leads to a sizable difference in the curve of the free energy of aggregation, that is nuclear quantum effects play a relevant role.